Peran Pendidikan Terhadap Pembentukan Sosial Siswa di Sekolah Dasar - Yuli Hana Puji Utami; Tutuk Ningsih (Jurnal Lensa Pendas, 2025)
Education plays an important role in shaping the character and social behavior of students, especially in elementary schools. The formation of students' sociality does not only occur through academic teaching, but also through social interactions at school, which involve relationships with peers, teachers, and the school environment as a whole. This article aims to analyze the role of education in the formation of students' sociality in elementary schools using the literature study method. This study examines various literature related to social education, school environment, and social interactions that support the development of students' character. The results of the study indicate that social education in schools has a significant role in developing students' social skills, such as empathy, cooperation, and responsibility. In addition, external factors such as support from family and community also contribute to the formation of students' sociality. The conclusion of this study confirms that education is not only aimed at improving students' academic abilities, but also at shaping students into individuals who are able to interact positively in society. The implication of this study is the need for close cooperation between schools, families, and communities to create an educational environment that supports the formation of students' sociality holistically, so that students can adapt well in diverse social environments.